Loss of Human Leukocyte Antigen Class I Expression Is Associated with Poor Prognosis in Patients with Advanced Breast Cancer - Hong Sik Park; Uiju Cho; So Young Im; Chang Young Yoo; Ji Han Jung; Young Jin Suh; Hyun Joo Choi (Korean Society of Pathologists & the Korean Society for Cytopathology, 2019)
Background Human leukocyte antigen class I (HLA-I) molecules play important roles in regulating immune responses. Loss or reduction of HLA-I expression has been shown to be associated with prognosis in several cancers. Regulatory T-cells (Tregs) also play critical functions in immune response regulation. Evaluation of HLA-I expression status by the EMR8-5 antibody and its clinical impact in breast cancer have not been well studied, and its relationship with Tregs remains unclear. Methods We evaluated HLA-I expression and Treg infiltration by immunohistochemistry in 465 surgically resected breast cancer samples. We examined the correlation between HLA-I expression and Treg infiltration and clinicopathologic characteristics and survival analyses were performed. Results Total loss of HLA-I expression was found in 84 breast cancer samples (18.1%). Univariate survival analysis revealed that loss of HLA-I expression was significantly associated with worse disease-specific survival (DSS) (p = .029). HLA-I was not an independent prognostic factor in the entire patient group, but it was an adverse independent prognostic factor for DSS in patients with advanced disease (stage II-IV) (p = .031). Treg numbers were significantly higher in the intratumoral stroma of HLA-I-positive tumors than in HLA-I-negative tumors (median 6.3 cells/high power field vs 2.1 cells/high power field, p < .001). However, Tregs were not an independent prognostic factor in our cohort. Conclusions Our findings suggest that the loss of HLA-I expression is associated with poor prognosis in breast cancer patients, highlighting the role of HLA-I alterations in immune evasion mechanisms of breast cancer. HLA-I could be a promising marker that enables the application of more effective and precise immunotherapies for patients with advanced breast cancer.